An Econometric Model of the Canadian Automobile Manufacturing Industry - David A. Wilton (Queen's University, Department of Economics, 1969)
This paper presents some results of a study which develops and tests an econometric model of the Canadian automotive manufacturing industry. Annual behaviour over the 1948-1964 period is examined by utilizing eighteen stochastic equations and four major identities. The research strategy follows conventional macro-econometric lines as it is hoped that such a key sector or satellite model can be integrated into a suitable Canadian macroeconomic model.
Keywords: 330